RANCANG BANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE PADA MTS DARUL ISLAH - Fajar Agung Nugroho; Muhaimin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
With the development of technology in this era, educational institutions should also adapt and take advantage of existing technological developments, one of which is in the process of managing data and disseminating information. At Mts Darul Islah the process of processing and conveying information related to students is still carried out in a conventional way. Given the Covid-19 pandemic that has occurred and also the role of increasingly advanced technology, this is no longer effective and efficient. Rapid Application Development (RAD) or Rapid Prototyping is a software development process model that belongs to the incremental technique. RAD emphasizes short, brief, and fast development cycles. With this school's academic information system, the school can manage academic data more efficiently. Students / parents of students can more easily obtain academic information without having to come to school.